The Effect of Endorphin Massage on Pain Intensity in the First Stage of the Active Phase of Labor at BPM Husniyati and BPM Yuhana Palembang - Fitria Resmi; Suprida; Rohaya; Desy Setiawati; Rina Nursanti (International Journal of Educational and Life Sciences, 2024)
Pain in labor is a subjective experience of physical sensations associated with uterine contractions, cervical dilation and effacement, and fetal descent during labor. To determine the effect of endorphin massage on pain intensity during the first active phase of labor at BPM Husniyati and BPM Yuhana Palembang This research uses a pre-experimental research method, with the design used is one group pre-test post-test. In this design, there was no control group, but an assessment was carried out before and after treatment was given. In this study, mothers in labor underwent pain measurements before and after being given endorphin massage to reduce labor pain. The results of the difference in pain were seen to see whether there was a decrease in labor pain before and after giving endorphin massage. This research was conducted at BPM Husniyati and BPM Yuhana Palembang in February-June 2018. The sampling technique in this study was purposive sampling, where sampling was based on criteria. As previously known, the sample size for simple experimental research using treatment groups is 30-500 samples. The sample taken in this study consisted of 30 respondents who were taken based on the number of mothers giving birth who met the inclusion criteria. research result for data before endorphin massage. Meanwhile, for the data after endorphin massage, the p value = 0.011. Because the p value <0.05, it can be concluded that the data distribution is not normal and further analysis uses the Wicoxon test. Conclusion The proportion of respondents who experienced severe pain intensity (7-9) before endorphin massage was 19 respondents (63.4%).